2009
DOI: 10.1111/j.1570-7458.2009.00862.x
|View full text |Cite|
|
Sign up to set email alerts
|

Host‐plant mediated interactions between two aphid species

Abstract: Herbivory induces numerous defence reactions in plants, which can in turn alter the plant quality for insects. The potato aphid, Macrosiphum euphorbiae (Thomas), and the green peach aphid, Myzus persicae (Sulzer) (both Hemiptera: Aphididae), are two important sympatric potato pests in northern France. The objective of this study was to evaluate the effect of a previous infestation of a potato plant, Solanum tuberosum L. (Solanaceae), by M. persicae or M. euphorbiae on the host attractiveness, feeding behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 56 publications
(63 reference statements)
0
25
0
Order By: Relevance
“…Aphids were reared on potato plants raised under the same conditions as above in a separated growth room. Experiments were conducted with alate aphids synchronized according to Brunissen et al (2009). The DC Electrical Penetration Graph system (Tjallingii 1978) was used to investigate aphid probing behaviour on the abaxial face of the third fully developed leaf of an infected or healthy plant.…”
mentioning
confidence: 99%
“…Aphids were reared on potato plants raised under the same conditions as above in a separated growth room. Experiments were conducted with alate aphids synchronized according to Brunissen et al (2009). The DC Electrical Penetration Graph system (Tjallingii 1978) was used to investigate aphid probing behaviour on the abaxial face of the third fully developed leaf of an infected or healthy plant.…”
mentioning
confidence: 99%
“…Additional work, however, has also shown that competition amongst two heterospecific aphids (Aphis fabae and A. pisum) feeding on a single cultivar of faba bean (Windsor) can change their preference for stem or leaves as a feeding site (Salyk and Sullivan, 1982). More recent studies have demonstrated that previous exposure to aphid herbivory can change the attractiveness of the host plant to subsequent herbivores (Brunissen et al, 2009) and similar effects may have occurred in our system. We suggest that the specific combination of host-plant genotype and the identity of the competitor species may be influencing the susceptibility of the host to P127, which in turn modifies aphid behaviour and choice of feeding site.…”
Section: Interspecific Competitionmentioning
confidence: 86%
“…For instance, sorghum susceptibility might increase if the plant was preinfested with aphids. This is associated with a reduction in the crystalline epidermal waxes on plant leaves (Gonzales et al 2002), whereas in most cases, preinfested hosts exhibit induced resistance against subsequent aphid infestations (Gomes et al 2005, Brunissen et al 2009). Future research should focus on responses to S. flava infestations in biofuel hosts.…”
Section: Discussionmentioning
confidence: 99%